Analysis of the Evolution of E-Business in the Channel Enhancement Stage in Retail Companies in Indonesia (Case study at PT Indomarco Prismatama (Indomaret)) - Elsa Zulfita; Deby Nofriansyah; Indah Wulan Sari Batubara; Nurbaiti Nurbaiti (Penerbit Jurnal Indonesia, 2022)
This study aims to find out how the evolution of e-business in the Channel Enhancement stage occurred in one of the largest retail companies in Indonesia. The sample of this research is PT Indomarco Prismatama (Indomaret). In this study, using a case study method with a qualitative approach. Data collection techniques were carried out using literature studies, observation and documentation studies. The results of this study indicate that the company PT Indomarco Prismatama or Indomaret has optimally utilized the development of information technology by implementing it into a website and digital application. Thus, the company has entered and implemented the Channel Enhancement evolution stage to the maximum extent.